Periodontal status, quality of life and newborns' health of pregnant women with arterial hypertension: A cohort study (Research, Society and Development, 2021)
This study aimed to evaluate, both during pregnancy and after delivery, the periodontal status and quality of life of women with gestational hypertension (GH). Secondarily, understanding the relationship between these outcomes and newborns’ health. The sample was divided into GH (G1 = 26) and without GH (G2 = 26) and evaluated regarding: a) contextual variables, b) systemic and periodontal status; and c) newborns’ health. ANOVA, Friedman, Cochran’s Q test, chi-squared test, and binary logistic regression were conducted (P < 0.05). A higher prevalence of women in G1 was diagnosed with pre-pregnancy obesity (P < 0.001). A higher prevalence of periodontitis was found in women in G1 in both periods (P < 0.001). The logistic model revealed that high maternal BMI (adjusted OR = 1.28; 95% CI = 1.10–1.47; P = 0.001) was associated with the presence of periodontitis. In both periods, G1 showed worse parameters related to physical pain and disability (P < 0.001), psychological discomfort and disability (P < 0.001). The logistic model revealed that periodontitis (adjusted OR = 11.64; 95% CI = 1.18–114.85; P = 0.036) was associated with a low quality of life. The groups did not show significant differences in the infants’ birth data. GH is associated with obesity and, together, seem to be associated with worsened periodontal parameters and, consequently, negative women’s quality of life. Children born to women with GH did not show any health impairment at birth.